Iron regulation of Shiga-like toxin expression in Escherichia coli is mediated by the fur locus. - Calderwood, S B (1987)
Shiga-like toxin is an iron-regulated cytotoxin quite similar to Shiga toxin from Shigella dysenteriae 1. The structural genes for Shiga-like toxin in Escherichia coli (sltA and sltB) appear to be transcribed as an operon from a promoter upstream of sltA. We used a gene fusion between the promoter and proximal portion of sltA with the gene for bacterial alkaline phosphatase to assess the regulation of toxin expression. Growth in low-iron conditions resulted in a 13- to 16-fold increase in alkaline phosphatase activity. In the presence of a null mutation in the fur locus, however, alkaline phosphatase activity was constitutively high regardless of the iron concentration. These data indicate negative regulation of the slt operon by the fur gene product. We used deletion analysis of the region upstream of the gene fusion to localize the promoter of the slt operon and to show that a region of DNA between the -35 and -10 boxes is necessary for iron regulation of slt expression. In this region, there is a 21-base-pair dyad repeat that is homologous to similar dyads in the promoter regions of three other fur-regulated genes. This region of dyad symmetry may represent an operator binding site for the Fur protein in the presence of iron.